2009
DOI: 10.4049/jimmunol.0902140
|View full text |Cite
|
Sign up to set email alerts
|

β-Defensins 2 and 3 Together Promote Resistance toPseudomonas aeruginosaKeratitis

Abstract: Defensins play an important role in both innate and adaptive immunity due to their antimicrobial, regulatory, and chemotactic effects. Nonetheless, the role of murine β-defensins (mBD) 3 and 4, the murine homologs of human β-defensins (hBD) 2 and 3, remains unknown in Pseudomonas aeruginosa keratitis. This study explored their role in corneal infection and potential synergy with mBD2, a defensin associated with better outcome in this disease. Immunostaining and real-time RT-PCR data demonstrated that mBD3 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
55
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 39 publications
9
55
0
Order By: Relevance
“…Furthermore, we demonstrated that recombinant hBD-2 has a strong antimicrobial effect on L. pneumophila, and silencing endogenous hBD-2 in alveolar epithelium increased intracellular replication of this pathogen. Our data is supported by observations of Wu and colleagues (43) who showed, with RNAi against mBD3 (homolog to hBD-2) in mice, an increased bacterial load of Pseudomonas aeruginosa in corneal infection. Thus, hBD-2 might be essential in controlling bacteria replication in the course of infections.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, we demonstrated that recombinant hBD-2 has a strong antimicrobial effect on L. pneumophila, and silencing endogenous hBD-2 in alveolar epithelium increased intracellular replication of this pathogen. Our data is supported by observations of Wu and colleagues (43) who showed, with RNAi against mBD3 (homolog to hBD-2) in mice, an increased bacterial load of Pseudomonas aeruginosa in corneal infection. Thus, hBD-2 might be essential in controlling bacteria replication in the course of infections.…”
Section: Discussionsupporting
confidence: 80%
“…Genotypes for Cnlp Ϫ/Ϫ , WT, and KO mBD3 mice were confirmed by standard PCR analysis done on DNA isolated from tail clips. In vivo knockdown of mBD4 was achieved using a method previously described by Wu et al using siRNA purchased from Santa Cruz Biotechnology (24). Briefly, 5 l of 8 M mBD4 siRNA or scrambled control siRNA was injected subconjunctivally into the right eye of C57BL/6 mice 1 day prior to fungal challenge.…”
Section: Methodsmentioning
confidence: 99%
“…The absorbance was measured for 90 min at 450 nm and plotted in comparison to a standard curve generated using purified MPO (Calbiochem, San Diego, CA) on the same plate (33). Results are expressed as relative units of MPO activity per cornea (1 MPO unit is proportional to 2 ϫ 10 5 infiltrating neutrophils) (23,24). HRT imaging.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations